KAJIAN SOSIAL EKONOMI USAHA BUDIDAYA UDANG VANNAMEI (LITOPENAEUS VANNAMEI) DI DESA DINOYO KECAMATAN DEKET KABUPATEN LAMONGAN - Dwi Zanuarita Chusnul; Jani Januar; Djoko Soejono (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2010)
Lamongan Regency is a potential area to develop the fishery industries for special is the area of embakment with the commodity of Vannamei shrimp in the Deket Subdistrict. There are some area in Deket Subdistrict with huge potential condition to cultivate Vannamei shrimp, one of them in Dinoyo Village. Dinoyo Village is the biggest producer of Vannamei shrimp and also it is easy to get the tradisional market which sell fish and Vannamei shrimp fry in order to be a potentially reason to develop the cultivation of Vannamei shrimp.Most of the resident of Dinoyo Village work as the farmer of Vannamei shrimp. However there are some problems faced by them, such as technical. Constraint like virus and the rarity of fertilizer, and also untechnical constraint like flood. This research is done to examine: the farmer’s motivation of Vannamei shrimp in Dinoyo Village, the social – economy factors which influence the income of Vannamei shrimp cultivation in Dinoyo Village, the efficiency of production expense usage in the Vannamei shrimp cultivation in DinoyoVillage.Key Words: Motivation of Shrimp, Income of Shrimp, and efficiency of production expense